The Effect of Mandated Child Care on Female Wages in Chile - María Prada; Graciana Rucci; Sergio Urzúa (Inter-American Development Bank (IDB), 2015)
This paper studies the effect of mandated employer-provided child care on the wages of women hired in large firms in Chile. We use a unique employer-employee database from the country's unemployment insurance (UI) system containing monthly information for all individuals that started a new contract between January 2005 and March 2013. We estimate the impact of the program using regression discontinuity design (RDD) exploiting the fact that child care provision is mandatory for all firms with 20 or more female workers. The results indicate that the monthly starting wages of the infra-marginal woman hired in a firm with 20 or more female workers is between 9 percent and 20 percent less than those of female workers hired by the same firm when no requirement of providing childcare was imposed.
hdl:11319/6880
Keywords: C21; J32; J71; J83; 330; Mandated benefits; female wages; regression discontinuity; policies for gender equality